(untitled) (Critical Journal of Social Sciences, 2026)
The Mid-Day Meal (MDM) Scheme is a government initiative in India that provides one free meal to students during school hours. It aims to improve nutritional outcomes, reduce dropout rates, and enhance school attendance. The school-age period represents a stage of rapid growth and development, during which adequate nutrition is essential. Students from low socio-economic families, in particular, require focused nutritional support. This study examines the nutritional and educational impact of the MDM Scheme on students. Fieldwork was conducted in two schools in Mapusa, Goa, involving a total of 122 students. Anthropometric data (height and weight) were recorded, and additional information on students’ demographic, educational, behavioural, socio-economic, and dietary characteristics was analyzed to understand the scheme’s impact. The results indicate that most daily consumers of MDM fall within the normal BMI range. However, the persistence of underweight students even among regular consumers suggests that the program does not fully meet students’ nutritional requirements. Socio-economic background also influences nutritional outcomes. The study highlights the need for greater menu diversity, as dissatisfaction with repetitive meals often leads to skipped lunches.